Chromogenic in situ hybridization compared with other approaches to evaluate HER2/neu status in breast carcinomas - Rosa, F.E.; Santos, R.M.; Rogatto, Silvia Regina [UNESP]; Domingues, M.A.C. (Associação Brasileira de Divulgação Científica (ABRADIC), 2013)
Human epidermal growth factor receptor 2 (HER2) has been evaluated in breast cancer patients to identify those most likely to benefit from herceptin-targeted therapy. HER2 amplification, detected in 20-30% of invasive breast tumors, is associated with reduced survival and metastasis. The most frequently used technique for evaluating HER2 protein status as a routine procedure is immunohistochemistry (IHC). HER2 copy number alterations have also been evaluated by fluorescence in situ hybridization (FISH) in moderate immunoexpression (IHC 2+) cases. An alternative procedure to evaluate gene amplification is chromogenic in situ hybridization (CISH), which has some advantages over FISH, including the correlation between HER2 status and morphological features. Other methodologies have also been used, such as silver-enhanced in situ hybridization (SISH) and quantitative real-time RT-PCR, to determine the number of HER2 gene copies and expression, respectively. Here we will present a short and comprehensive review of the current advances concerning HER2 evaluation in human breast cancer.
Keywords: CISH; Breast cancer; HER2; Immunohistochemistry; FISH